Synergistic Antibacterial Effects of Amoxicillin and Gold Nanoparticles: A Therapeutic Option to Combat Antibiotic Resistance - Rosa M. Giráldez-Pérez; Elia M. Grueso; Alfonso Carbonero; Juan Álvarez Márquez; Mirian Gordillo; Edyta Kuliszewska; Rafael Prado-Gotor (MDPI AG, 2023)
Compacted Au@16-mph-16/DNA-AMOX (NSi) nanosystems were prepared from amoxicillin (AMOX) and precursor Au@16-mph-16 gold nanoparticles (Ni) using a Deoxyribonucleic acid (DNA) biopolymer as a glue. The synthesized nanocarrier was tested on different bacterial strains of Escherichia coli, Staphylococcus aureus, and Streptococcus pneumoniae to evaluate its effectiveness as an antibiotic as well as its internalization. Synthesis of the nanosystems required previous structural and thermodynamic studies using circular dichroism (CD) and UV-visible techniques to guarantee optimal complex formation and maximal DNA compaction, characteristics which facilitate the correct uptake of the nanocarrier. Two nanocomplexes with different compositions and structures, denoted NS1 and NS2, were prepared, the first involving external Au@16-mph-16 binding and the second partial intercalation. The Ni and NSi nanosystems obtained were characterized via transmission electron microscopy (TEM), zeta potential, and dynamic light scattering (DLS) techniques to measure their charge, aggregation state and hydrodynamic size, and to verify their presence inside the bacteria. From these studies, it was concluded that the zeta potential values for gold nanoparticles, NS1, and NS2 nanosystems were 67.8, −36.7, and −45.1 mV. Moreover, the particle size distribution of the Au@16-mph-16 gold nanoparticles and NS2 nanoformulation was found to be 2.6 nm and 69.0 nm, respectively. However, for NS1 nanoformulation, a bimodal size distribution of 44 nm (95.5%) and 205 nm (4.5%) was found. Minimal inhibitory concentration (MIC) values were determined for the bacteria studied using a microdilution plates assay. The effect on Escherichia coli bacteria was notable, with MIC values of 17 µM for both the NS1 and NS2 nanosystems. The Staphylococcus aureus chart shows a greater inhibition effect of NS2 and NP2 in non-diluted wells, and clearly reveals a great effect on Streptococcus pneumoniae, reaching MIC values of 0.53 µM in more diluted wells. These results are in good agreement with TEM internalization studies of bacteria that reveal significant internalization and damage in Streptococcus pneumoniae. In all the treatments carried out, the antibiotic capacity of gold nanosystems as enhancers of amoxicillin was demonstrated, causing both the precursors and the nanosystems to act very quickly, and thus favoring microbial death with a small amount of antibiotic. Therefore, these gold nanosystems may constitute an effective therapy to combat resistance to antibiotics, in addition to avoiding the secondary effects derived from the administration of high doses of antibiotics.